THE BEZOARS: CLASSIFICATION, DIAGNOSIS, TREATMENT AND CLINICAL CASES - REVIEW - Magdalena Maria Jakubowska,; Weronika Wawrzynów,; Agnieszka Skoczeń,; Aleksandra Dorosz,; Błażej Kaczmarek,; Adrian Kruk,; Dominika Walczak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Bezoars are foreign bodies found mainly in the gastrointestinal tract (but not exclusively) giving non-specific and sparse symptoms, which can contribute to serious complications such as chronic mucositis, intestinal obstruction, peritonitis, sepsis and in some cases can even lead to death. A distinction can be made between trichobezoars, phytobezoars, lactobezoars, pharmacobezoars and urinary tract bezoars. Endoscopic examination plays a major role in diagnosis.[1]Objective: The aim of this review is to provide information on the origin, classification, diagnosis and treatment of bezoars and to present several clinical cases involving different types of bezoars.Methods and materials: For the literature review, a Pubmed database and Polish websites of renowned medical journals were used, using keywords such as: bezoar, trichobezoar, phytobezoar, lactobezoar, pharmacobezoar.